Effect of V-type crystallinity and starch particle structure on the oil loading capacity and anti-oxidation - Wu, Chenbei; Junejo, Shahid Ahmed; Zhang, Bin; Fu, Xiong; Tan, Chin Ping; Huang, Qiang (Elsevier, 2022)
Starch-based carriers have a great potential in functional oil encapsulation because of their mild preparation conditions, but the oil loading capacity and underlying anti-oxidation mechanism remain unclear. Here V-type starches were applied to fabricate flaxseed oil powder. Particle size analysis and scanning electron microscopy showed a loose aggregation microstructure of normal maize starch (NMS) prepared using the anti-solvent (AS) precipitation method, with an average size of 24.9 μm. Differential scanning calorimetry displayed a good thermo-oxidation resistance of NMS-derived V-type starch prepared via AS precipitation. Principal component analysis revealed that the oil loading capacity, related closely to V-type crystallinity and D50, has a significant positive correlation with the onset oxidation temperature and a negative correlation with the peroxide, thiobarbituric acid, and ρ-anisidine values. Our original study reveals the effects of V-type crystallinity and aggregation microstructure on the oil loading capacity and anti-oxidation, providing theoretical guidance for developing novel, starch-based carriers.